Diversity and distributions of circumpolar fresh- and brackish-water Mysis (Crustacea: Mysida): descriptions of M. relicta Loven, 1862, M. salemaai n. sp., M. segerstralei n. sp. and M. diluviana n. sp., based on molecular and morphological characters - Audzijonyte, A; Vainola, R (Hydrobiologia, 2005)
Mysid crustaceans of the Mysis relicta species group are widespread throughout the northern Holarctic and play an important role in many fresh- and brackish-water ecosystems. Earlier molecular and morphometric studies already indicated that the conventionally identified Mysis relicta sensu lato comprises several distinct species. Here we present formal taxonomic diagnoses, descriptions and an account of the distributions of Mysis relicta s. str. and three new species split from it, based on comprehensive assessment of both morphological and molecular characters (allozymes, mtDNA). M. relicta Lovn s. str. is the prevalent species in lakes of Northern Europe and peripheral parts of the brackish Baltic Sea. M. salemaai n. sp. inhabits offshore habitats of the Baltic Sea and a range of lakes from the British Isles, southern Scandinavia and Karelia to coastal northern Siberia; at several sites M. relicta and M. salemaai are sympatric. M. segerstralei n. sp. has a circumpolar distribution along the Arctic coasts and islands of Eurasia and North America and also occurs in lakes of these northern regions. M. diluviana n. sp. inhabits continental freshwater lakes of the once-glaciated northern North America. The four species are characterised by unique combinations of alleles at a number of allozyme loci, and most of them by specific mitochondrial DNA lineages diverged by c. 7.5% in the COI gene sequence (cytochrome oxidase subunit I). The most important diagnostic morphological characters include the shape of the posterior emargination of carapace, length of setae on the merus of maxillipede 2, length and shape of spine-setae on maxilla endopod distal segment, number and size of lateral spine-setae on telson, and setation of thoracic endopods. A morphological key to the four species is presented.